Singapore's hardcore punk subculture : an ethnographic approach - Elamaaran, B. (2009)
This paper looks at the little known and even less understood hardcore punk subculture in Singapore, arguably the largest and most visible group in the local underground music scene. This subculture has its own unique style of music, dance, fashion, and even media. Combining ethnographic field work and methods of visual research, this paper look sat this subculture's communication process. In particular, the use of cameras plays a significant part in revealing how subcultural style is used as symbolic communication. The use of cameras reveals contradictions in the subculture. The study also looks at the subculture's camera and how the subculture appropriate the researchers' cameras for the purpose of correcting mainstream misconceptions about them.